Analisis Akuntabilitas Pengelolaan Dana Otonomi Khusus Papua - Junaedi, Ahmad; suswanta, suswanta (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
The impact of this inadequate management of funds resulted in the absence of significant benefits in promoting the welfare of the community. In a report prepared by (Secretary General and BK DPR RI, 2020) it is explained that based on the mandate of Law No.21 of 2001 concerning Special Autonomy for Papua Province paragraph (3), the special autonomy fund is intended to finance education and health. Therefore, in remembrance of the law, the ideals of giving special autonomy are to reduce inequality, improve the standard of living, and the welfare of the people, especially in the Provinces of Papua and West Papua. However, these ideals do not seem to be running optimally, one of which is due to problems in the Otsus funding flow. Therefore, this paper is aimed at seeing how the Papua Special Autonomy policy program, especially in West Papua, is in the welfare of the community and what obstacles are encountered in terms of accountability. In this paper, the authors conducted research using qualitative methods with the stages: data collection, data analysis and report writing. For data collection, the authors use library research (library research). The existing data shows that even though there is a trend of increasing HDI in Papua and West Papua Provinces, the increase in HDI in these two provinces still occupies the lowest position among 34 Provinces throughout Indonesia. In the period of 20 years, the implementation of Special Autonomy still leaves problems, especially in the issue of special autonomy fund management, so that the impact of the ineffectiveness of the use of these funds has an impact on the slow growth of community welfare. Apart from that, the existence of political factors that often become obstacles to the management of these funds also presents a challenge in itself. This is based on the fact that the application of Otusus in previous years still experienced the same problems. Therefore, in the future we need a policy that can firmly regulate the performance audit of Otsus funds in Papua and West Papua. This is because one of the major problems that hinders the effective use of Otsus is about its accountability.